Estudio seroepidemiologico de la tripanosomiasis bovina en el departamento de Córdoba-Colombia (1992)
The present studies were conducted as part of the activities of the Colombo-German ICA-GTZ Animal Health Project. The prevalence of Tnpanosonc viiar was investigated using the IFAT technique in 385 bovines divided into four groups according to age. The results showed a 46.2 ± 2.540/a (p 0.05) infection rate for the area. The prevalence ranged from 36.6 ± 8.79% (pO.05) in Moñitos to 76.9 ± 7.67% in Lorica. Infection rates were different (p!~0.05) between age groups being 50.9 ± 6.860/6 for the 1-6 months group and 42.0 ± 3.9% for animals about 24 months. According to the results the tripanosome is widely distributed in Cordoba which in agreement with other results that proved the area is endemic for T.